2010
DOI: 10.1111/j.1365-2095.2010.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary betaine levels on growth performance and hepatic intermediary metabolism of GIFT strain of Nile tilapia Oreochromis niloticus reared in freshwater

Abstract: An 8‐week feeding experiment was conducted to determine the effect of dietary betaine levels on the growth performance and hepatic intermediary metabolism of genetically improved farmed tilapia (GIFT) strain of Nile tilapia Oreochromis niloticus (mean initial body weight: 78.3 ± 1.3 g, means ± SD). Six practical diets were formulated with the incorporation of betaine at the levels of 0 (control), 5, 10, 15, 20 and 25 g kg−1. Survival showed no significant differences among the treatments (P > 0.05). The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
8
36
1
Order By: Relevance
“…In this study, significantly higher FBW and SGR were observed in allogynogenetic gibel carp fed the diet containing 0.4% betaine than in the control group (p < .05). Similar results have also been delivered in gibel carp and Nile tilapia, in which 0.5% betaine supplementation showed growth-and feeding-enhancing effects (Luo, Tan, Liu, & Wen, 2011;Xue & Cui, 2001). In addition, 2% dietary betaine resulted in none growthenhancing effect compared to the control group in the present study, which is similar to the finding in blue tilapia that betaine sup- T A B L E 2 Growth performance and feed utilization of the experimental diets (means AE SEM)* and feed utilization in both fresh and sea water conditions (Genc, Tekelioglu, Yilmaz, Hunt, & Yanar, 2006).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…In this study, significantly higher FBW and SGR were observed in allogynogenetic gibel carp fed the diet containing 0.4% betaine than in the control group (p < .05). Similar results have also been delivered in gibel carp and Nile tilapia, in which 0.5% betaine supplementation showed growth-and feeding-enhancing effects (Luo, Tan, Liu, & Wen, 2011;Xue & Cui, 2001). In addition, 2% dietary betaine resulted in none growthenhancing effect compared to the control group in the present study, which is similar to the finding in blue tilapia that betaine sup- T A B L E 2 Growth performance and feed utilization of the experimental diets (means AE SEM)* and feed utilization in both fresh and sea water conditions (Genc, Tekelioglu, Yilmaz, Hunt, & Yanar, 2006).…”
supporting
confidence: 71%
“…To date, however, little information is available on the effects of dietary betaine on lipid accumulation in fish. In tilapia, betaine supplementation in the diet significantly increased growth performance, but showed no significant effect on liver composition (Luo et al., ). In the present study, lipid content in the hepatopancreas, muscle and the whole body was significantly reduced by dietary betaine addition in VB 0.4 group, while no significant difference was detected in VB 0.08 and VB 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genç and Tekelioğlu () reported best WG in juvenile sea bass ( Dicentrarchus labrax ) for 2% L‐glutamic acid‐supplemented group (62.17 ± 1.26 g) followed by 2% betaine‐supplemented group (54.41 ± 1.55 g). Luo, Tan, Liu, and Wen () reported the best live gain in the Nile tilapia ( Oreochromis niloticus ) for 0.05% betaine‐supplemented group (150.6 ± 2.7 g), whereas the weight gain was 111.3 ± 3.6 g in control group. Shankar, Murthy, Pavadi, and Thanuja () conducted a study with fingerlings of Rohu fish and reported WGs of 20.4 g and 16.5 g for the 0.25% betaine‐supplemented and the control groups respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the most recognized feed stimulatory effectors include amino acids, betaine, 2‐carboxy‐ethyl dimethyl sulphonium bromide (DMPT), nucleotides and nucleosides, and some mixtures (such as squid extract, fish soluble and krill meal) (Nakajima, Uchida, & Ishida, ; NRC, ). Their beneficial effects to aquaculture species, such as the enhancement of feed intake and improvement of growth performance, are now widely recognized in many aquatic species (Li & Gatlin, ; Luo, Tan, Liu, & Wen, ; Suresh, Kumaraguru Vasagam, & Nates, ; Whirley & Einat, ). However, the aforementioned studies usually focused on fish and shellfish, and literatures concerning the investigation of diet preference by reptile are quite limited.…”
Section: Introductionmentioning
confidence: 99%